Simulation-based optimization at container terminals: A literature review - Marvin Kastner; Hannah Pache; Carlos Jahn (Digital Transformation in Maritime and City Logistics: Smart Solutions for Logistics. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 28, 2019)
Purpose: While simulation-based optimization has been discussed in theory and practically employed at container terminals, the different publications in this field have not yet been presented and compared in a structured manner. This paper gathers the latest developments and examine the similarities and differences of the provided approaches. Furthermore, research gaps are identified. Methodology: The recent literature of simulation-based optimization on container terminals is examined using a mapping review approach. Emphasis is laid on the covered problems, chosen meta-heuristics, and the shapes of the solution space. Findings: In the applied literature of container terminals genetic algorithms prevail, both for scheduling problems and for the determination of discrete and/or continuous parameters. Because of the no-free-lunch-theorem for optimization, it is open whether the chosen optimization approach serves the purpose best. Originality: To the best of our knowledge, the existing literature regarding simulation- based optimization at container terminals has never been addressed in a detailed overview. The elaborated comparison of the different publications leads to further research directions.
urn:nbn:de:gbv:830-882.054664; 10419/209197; https://econpapers.repec.org/RePEc:zbw:hiclpr:28
Keywords: 650; Simulation-based optimization; Simulation-based optimisation; Container terminal; Maritime logistics